Insulin‐like growth factor I enhances the developmental competence of yak embryos by modulating aquaporin 3. (16th May 2017) - Chen, P; Pan, Y; Cui, Y; Wen, Z; Liu, P; He, H; Li, Q; Peng, X; Zhao, T; Yu, S
Contents: The objective of our present study was to determine the effects of insulin‐like growth factor I (IGF‐I) on the development of yak ( Bos grunniens ) embryos after cumulus–oocyte complex (COC) vitrification and warming followed by in vitro fertilization (IVF). In Experiment 1, the yak COCs underwent vitrification and then IVF. Embryos were incubated in synthetic oviductal fluid (SOF) supplemented with four concentrations (0, 50, 100 and 200 ng/ml) of IGF‐I, while the yak COCs without vitrification or IGF‐I supplementation acted as the control group; the BAX, BCL‐2, AQP3 mRNA and aquaporin 3 (AQP3) protein expression levels in the five groups of blastocysts were evaluated using quantitative real‐time PCR and immunofluorescence analyses. In Experiment 2, the groups described above were fertilized and incubated. The cleavage rate, blastocyst rate, total cell count per blastocyst and the rate of growth of the inner cell mass (ICM) and trophectoderm (TE) were evaluated. The results were as follows: (1) the AQP3 gene expression and protein expression in the control and 100 ng/ml IGF‐I treatment groups were the highest. (2) The BAX gene expression was the lowest and the BCL‐2 gene expression was the highest in the control and 100 ng/ml IGF‐I treatment groups. (3) The rates of cleavage and blastocysts in the control and 100 ng/ml IGF‐I groups were higher than those in the other three groups. The total cell count per blastocyst in the vitrified and warmed 100 ng/ml IGF‐I group (106.7 ± 4.9) and the control group (107.3 ± 4.2) was higher than that in the vitrified and warmed 0 ng/ml IGF‐I (91.2 ± 3.1), 50 ng/ml IGF‐I (92.3 ± 3.7) and 200 ng/ml IGF‐I (92.4 ± 3.7) groups. Therefore, we conclude that IGF‐I can improve yak blastocyst developmental ability, cytomembrane permeability and formation of the blastocyst cavity after COC vitrification by improving the BAX, BCL‐2 and AQP3 expression levels.